Caracterização morfológica e composição bioquímica de genótipos de soja portadores de genes piramidados de resistência a Phakopsora pachyrhizi - Panho, Maiara Cecilia (2022)
Asian rust (ASR, Phakopsora pachyrhizi Sydow and Sydow) is the main disease of the crop, causing major drops in soybean yield, affecting the entire grain market. With the low efficiency of fungicides, the use of resistant cultivars is presented as an alternative control, being economical, safe, efficient and sustainable. However, due to the great variability and aggressiveness of ASR, the use of Rpp genes is limited. Thus, the pyramiding of resistance genes is shown as an alternative in the search for cultivars with higher levels of resistance. However, identifying the most suitable combination of genes that will result in genotypes with high levels of resistance needs to be studied. In this way, understanding which resistance mechanisms are involved in the soybean-P. pachyrhizi, can help breeding programs to develop combinations with higher levels of resistance. The objective of the present study was to identify morphological, phenotypic and biochemical variability of genotypes (cultivars, lines and PI's – plant introduction) containing different combinations of pyramided genes (Rpps) of resistance to ASR, aiming to identify the defense mechanisms associated with resistance genes. Sibling lines containing pyramided Rpp genes, plant introductions (PIs) and resistant and susceptible cultivars were evaluated for FAS resistance at field level. The phenotypic characteristics (resistance lesion: Reddish brown, susceptible and immune) and resistance characters: number of uredia per lesion (NoU), frequency of lesion with uredia (%LU), sporulation level (SL), and area under the disease progress curve (AUDPC), morphological characteristics: upper (UET) and lower (LET) epidermis thickness, palisade (PPT) and spongy (SPT) parenchyma thickness and leaf limb thickness (LLT); and biochemical characteristics (phenolic compounds): daidzin, glycitein, daidzein, genistein and genistin. All strains with pyramided Rpp genes showed high levels of resistance, with significant reductions in SL, NoU and %LU compared to sources of resistance. All genotypes of combinations Rpp1-b + Rpp1-b, Rpp2 + Rpp1-b, Rpp4 +Rpp1-b, in addition to the Rpp1-b gene were classified as “high resistant” (HR). In addition, strain 52117-57 (Rpp2 + Rpp1-b) showed immunity under field conditions. All genotypes classified as HR had the lowest AUDPCs. The susceptible genotypes had the highest AUDPCs, highlighting the importance of genetic resistance in containing the disease progression. The morphological and biochemical characters evaluated in the present study were not related to the ASR resistance Rpp genes. Thus, further studies are needed to investigate which other structural and biochemical mechanisms may be involved in the process of soybean resistance to ASR.